ANALYSIS OF CARDIOVASCULAR CAPACITY OF ELEMENTARY SCHOOL STUDENTS BASED ON BODY MASS INDEX (BMI) CATEGORY - Sandrorium, Sandrorium; Robi, La; Mawardi, Muh; Kurniadi, Agus; Anggraeni, Emayanti (Faculty of Teacher Training and Education, 2026)
This study aims to analyze the relationship between Body Mass Index (BMI) and cardiovascular capacity (VO₂max) in elementary school students in Sorong City. Cardiovascular fitness, as measured by the Multi Stage Fitness Test (MSFT), is an important indicator in assessing children's health and physical endurance. This study used a cross-sectional design with a sample of 50 students in grades V and VI. The results showed that 60% of students with normal BMI had good cardiovascular capacity, while students with overweight and obese BMI tended to have lower capacity. Pearson correlation analysis produced a value of r = -0.65 (p <0.01), indicating a significant negative relationship between BMI and VO₂max. This finding emphasizes that excess body fat has a negative impact on the efficiency of the cardiovascular system and the body's capacity to transport oxygen during physical activity. Therefore, attention to nutritional status and increasing physical activity from an early age is very important in maintaining children's heart and lung fitness